The role of system justification theory in support of the government under long-term conservative party dominance in Japan - Nakagoshi, Mizuki; Inamasu, Kazunori (Frontiers in Psychology, 2023)
The applicability of system justification theory (SJT) in Japan, where political contexts differ from those in Western countries, was evaluated in this study. SJT explains the psychological mechanisms underlying conservatism. Japan, which has a relatively long history as a democracy among East Asian countries, has a special political context. For instance, (1) it has had almost uninterrupted conservative governance since the end of World War II; and (2) unlike Western countries, opinions on economic issues are not clearly linked to conservative attitudes. A web survey of Japanese voters (n=1,428) revealed that high general system justification (GSJ) and economic system justification (ESJ) were correlated with conservatism. Further, path analysis results showed that GSJ and ESJ predicted conservative attitudes. Additional analysis suggested that the status-legitimacy hypothesis, in which lower status groups have higher system justification motives, is not supported.